Correlation Between Hashimoto's Thyroiditis–Related Thyroid Hormone Levels and 25-Hydroxyvitamin D - Chao, Guanqun; Zhu, Yue; Fang, Lizheng (Frontiers in Endocrinology, 2020)
Objective:The purpose of this study was to further clarify the association of Hashimoto’s thyroiditis(HT) and vitamin D deficiency, and to seek the connection between them and related influencing factors. Methods: Datas were obtained from subjects who underwent health examination from January 2018 to December 2018The diagnosis of HT was based on: antithyroid peroxidase antibody (TPO-Ab) levels >35 IU/mL, and/or antithyroglobulin antibody (Tg-Ab) levels >40 IU/mL. Based on the Endocrine Society guidelines,  25-Hydroxyvitamin D(25(OH)D) levels ≥30.0 ng/mL were classified as a vitamin D sufficiency; those between 20 and 29.9 ng/mL, as an insufficiency; and those <20 ng/mL, as a deficiency.All statistical analysis was performed by software R. Results: Of a total of 75,436 individuals who were physically examined, 5656 of them had 25 (OH) D levels tested at the same time,5230 were enrolled.The level of 25 (OH) D in the non-HT group was higher than that in the HT group.Multiple regression analysis showed that HT was statistically significantly correlated with male, BMI, waist circumference and TSH.TSH levels in the Insufficiency group and Deficiency group were higher than those in the Sufficiency group.FT3 and FT4 levels in the Insufficiency group and Deficiency group were lower than those in the Sufficiency group. 25(OH)D increased by 1 ng/ml at the normal reference level, with an increase of 2.78 ng/dl in FT4 concentration and a decrease of 0.17 mIU/L in TSH. Conclusions: Patients with HT present with reduced 25(OH)D level, and TSH are independent risk factors for HT.TSH is negatively correlated with 25(OH)D level.FT3 and FT4 levels were positively correlated with 25(OH)D levels.